Risk Factors of Intravenous Immunoglobulin Resistance in Children With Kawasaki Disease: A Meta-Analysis of Case-Control Studies - Liu, Gengying; Wang, Shunyu; Du, Zhongdong (Frontiers in Pediatrics, 2020)
Previous studies have shown that children with Kawasaki disease (KD) who fail to respond to intravenous immunoglobulin (IVIG) therapy are at higher risk of developing coronary artery abnormalities. We aimed to conduct a meta-analysis to uncover the risk factors that were closely related to IVIG resistance in children with KD. PubMed, Embase and Cochrane Library databases were searched up to 31st October 2019, 23 case-control studies were finally eligible, enrolling 2053 patients of IVIG resistance and 16635 patients of IVIG sensitivity. We comprehensively analyzed potential factors using stata15 software with a standard meta-analysis procedure and consequently found that in addition to patients with polymorphous rash or swelling of extremities symptom had a tendency to be non-responders, IVIG resistance was more likely to occur in patients with severe anemia, hypoalbuminemia, lower baseline platelet count, and higher erythrocyte sedimentation rate (ESR), bilirubin, alanine aminotransferase (ALT) and percentage of neutrophils. Particularly, male sex, hyponatraemia, high aspartate aminotransferase (AST) and C-reactive protein (CRP) were confirmed as the risk factors favor IVIG resistance in Mongoloid patients from Asia countries, but not in Caucasians from non-Asia regions. White blood cell count, age, conjunctivitis, oral changes and cervical lymphadenopathy were identified as unrelated factors. In summary, we report various risk factors and irrelevant factors of IVIG resistance in children with KD and recommend clinicians consider these factors closely, a reduction in coronary artery lesions (CAL) rates is prospectively expected with accurate prediction and timely aggressive initial treatment in high-risk patients.